FAKTOR-FAKTOR PENENTU TINGKAT PARTISIPASI PEDAGANG DALAM PENGELOLAAN SAMPAH DI PASAR PAGI ARENGKA KOTA PEKANBARU - Zulkarnaini Zulkarnaini; Zulfan Saam (Program Pascasarjana Universitas Riau, 2009)
Garbage is the one of environmental problems that still unhandled. One complicated problem isgarbage in market had increased relatively and problematically. Trader participation hadinfluenced of garbage management of market. The results had showed that trader participationtrader in garbage management at morning market of Arengka Pekanbaru was moderately. Thedeterminant factors had influenced participation level was education, earning, garbage cares,regulation, environmental condition and facilities.